Common Fixed Point Theorems Under Strict Contractive Conditions in Fuzzy Metric Spaces - Rani, Rashmi (Asian Journal of Science and Applied Technology, 2018)
Fuzzy sets originally introduced Zadeh. Using Concept of fuzzy sets, various theories regarding giving new concepts of fuzzy metric spaces were considered by various authors. After that, many authors have studied fixed point theory in such spaces and proved various fixed point theorems in such spaces. In 1975, Kramosilet al. have introduced the concept of fuzzy metric spaces. In this paper, using concept of fuzzy metric space given by Kramosil et al., we prove common fixed point theorems for weakly compatible mappings satisfying strict contractive condition in fuzzy metric spaces by using property (E.A). Our proved results generalize known fixed point theorems in literature. We prove two common fixed point theorems in this paper, one for four maps and other one for two maps. Mathematics subject classification: 54E40, 54E35, 54H25.